The neuroanatomy of subthreshold depressive symptoms in Huntington's disease: a combined diffusion tensor imaging (DTI) and voxel-based morphometry (VBM) study. Issue 9 (July 2014) - Sprengelmeyer, R.; Orth, M.; Müller, H.-P.; Wolf, R. C.; Grön, G.; Depping, M. S.; Kassubek, J.; Justo, D.; Rees, E. M.; Haider, S.; Cole, J. H.; Hobbs, N. Z.; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Depressive symptoms are prominent psychopathological features of Huntington's disease (HD), making a negative impact on social functioning and well-being. Method We compared the frequencies of a history of depression, previous suicide attempts and current subthreshold depression between 61 early-stage HD participants and 40 matched controls. The HD group was then split based on the overall HD group's median Hospital Anxiety and Depression Scale-depression score into a group of 30 non-depressed participants (mean 0.8, s.d. = 0.7) and a group of 31 participants with subthreshold depressive symptoms (mean 7.3, s.d. = 3.5) to explore the neuroanatomy underlying subthreshold depressive symptoms in HD using voxel-based morphometry (VBM) and diffusion tensor imaging (DTI). Results Frequencies of history of depression, previous suicide attempts or current subthreshold depressive symptoms were higher in HD than in controls. The severity of current depressive symptoms was also higher in HD, but not associated with the severity of HD motor signs or disease burden. Compared with the non-depressed HD group DTI revealed lower fractional anisotropy (FA) values in the frontal cortex, anterior cingulate cortex, insula and cerebellum of the HD group with subthreshold depressive symptoms. In contrast, VBM measures were similar in both HD groups. A history of depression, the severity of HD motor signs or disease burden did not correlate with FA values of these regions. Conclusions Current subthreshold depressive symptoms in early HD are associated with microstructural changes – without concomitant brain volume loss – in brain regions known to be involved in major depressive disorder, but not those typically associated with HD pathology.